Spatiotemporal changes and influencing factors of ecosystem services in the Nanchang metropolitan area, China - Zhang, Ting; Hu, Yuzhu; Guan, Shengyu; Zhu, Mianxuan; Lei, Tingting; Hu, Haihui (Frontiers in Ecology and Evolution, 2024)
Ecosystem services (ES) such as carbon storage (CS), soil conservation (SC), habitat quality (HQ), and water yield (WY) play a crucial role in maintaining ecological balance and supporting sustainable regional development. With increasing environmental changes, understanding the spatiotemporal dynamics of these services and their driving factors has become essential in environmental science. This study focuses on the Nanchang metropolitan area, quantifying CS, SC, HQ, and WY from 2000 to 2020. It explores the impacts of major factors, including climate, topography, and social aspects, on the spatial heterogeneity of ES. The results reveal that between 2000 and 2020, CS and HQ decreased by 0.1385×108 tons/ha and 0.0507, respectively, while SC and WY increased by 2.4754×109 tons/ha and 1.6668×1010 m3, respectively. Notable spatial heterogeneity exists in the correlation between driving factors and changes in ES. The spatial distribution of ESs is higher in mountainous regions compared to central plains. Among human factors, population (POP) and gross domestic product (GDP) predominantly influenced changes in CS and HQ, whereas climate and POP drove changes in SC. Changes in WY were primarily affected by climate and topography. These findings suggest a need to focus on key driving factors to formulate targeted land policies aimed at enhancing the ES value in the Nanchang metropolitan area.